The Role of Protein Kinase Cη in T Cell Biology - Gascoigne, Nicholas R. (Frontiers in Immunology, 2012)
Protein kinase Cη (PKCη) is a member of the novel PKC subfamily, which also includes δ, ε, and θ isoforms. Compared to the other novel PKCs, the function of PKCη in the immune system is largely unknown. Several studies have started to reveal the role of PKCη, particularly in T cells. PKCη is highly expressed in T cells, and is upregulated during thymocyte positive selection. Interestingly, like the θ isoform, PKCη is also recruited to the immunological synapse that is formed between a T cell and an antigen-presenting cell. However, unlike PKCθ, which becomes concentrated to the central region of the synapse, PKCη remains in a diffuse pattern over the whole area of the synapse, suggesting distinctive roles of these two isoforms in signal transduction. Although PKCη is dispensable for thymocyte development, further analysis of PKCη− or PKCθ−deficient and double knockout mice revealed the redundancy of these two isoforms in thymocyte development. In contrast, PKCη rather than PKCθ, plays an important role for T cell homeostatic proliferation, which requires recognition of self-antigen. Another piece of evidence demonstrating that PKCη and PKCθ have isoform specific as well as redundant roles come from the analysis of CD4 to CD8 T cell ratios in the periphery of these knockout mice. Deficiency in PKCη or PKCθ had opposing effects as PKCη knockout mice had a higher ratio of CD4 to CD8 T cells compared to that of wild-type mice, whereas PKCθ-deficient mice had a lower ratio. Biochemical studies showed that calcium flux and NFκB translocation is impaired in PKCη-deficient T cells upon TCR crosslinking stimulation, a character shared with PKCθ-deficient T cells. However, unlike the case with PKCθ, the mechanistic study of PKCη is at early stage and the signaling pathways involving PKCη, at least in T cells, are essentially unknown. In this review, we will cover the topics mentioned above as well as provide some perspectives for further investigations regarding PKCη.